How boundary objects facilitate local climate adaptation networks: the cases of Amsterdam Rainproof and Water Sensitive Rotterdam. Issue 7 (7th June 2023) - Willems, Jannes J.; van Popering-Verkerk, Jitske; van Eck, Lucy
Abstract : New networks of public and private parties co-produce urban climate adaptation measures, for which different viewpoints and interests have to be bridged. While previous research has focused on individuals and organizations as intermediaries, little attention has been paid to boundary objects: conceptual or material objects that help to bridge competing values. This article aims to understand how local climate adaptation networks co-develop boundary objects and how they benefit the development of adaptation measures by conducting a qualitative case study comparison of two front-running Dutch networks: Amsterdam Rainproof and Water Sensitive Rotterdam. The conceptualization of a "water-sensitive city" attracted multiple stakeholders (professionals from different disciplines, communities, businesses), while material objects, such as interactive 3 D-models, addressed information needs. The objects contributed to adaptation measures by convening stakeholders, translating viewpoints and initiating collaborations. The limited diversity in the networks suggests that, rather than enabling participatory decision-making, the networks are instrumentally used by water authorities.